Modulating gut microbiota with SCFAs and high-fiber diets to mitigate PM2.5-induced hypertension in mice - Kaixin Yan; Siyuan Wang; Minjie Wang; Yaxuan Yao; Xiaoyan Liu; Jiawei Song; Yihang Chen; Yufei Chen; Ruiqiang Qi; Xinyu Zhou; Jiuchang Zhong; Chaowei Hu; et al. (Ecotoxicology and Environmental Safety)
Exposure to PM2.5 is recognized to significantly impact the development of cardiovascular diseases, particularly hypertension, which has been recently attributed to an abnormal microenvironment characterized by disordered gut microbiota. Despite this recognition, the impacts of modulating gut microbiota with short chain fatty acids (SCFAs) and high-fiber diets (HF) on mitigating PM2.5-induced hypertension remain unclear. Our study demonstrates that mice supplemented with SCFAs or a HF exhibit reduced blood pressure, improved vascular remodeling, and alleviated gastrointestinal tract damages compared to those exposed to PM2.5 alone. These dietary interventions altered the gut microbiota composition of PM2.5-exposed mice, including alpha-diversity, beta-diversity patterns, and enriched profiles of intestinal microbes such as Lactobacillus, Bacteroides, and Ruminococcaceae. Furthermore, SCFAs and HF modulated the fecal metabolome by increasing the abundance of metabolites like Bufalin, Glycocholic acid, Syringaresinol and Equol. These microbial and metabolic alterations are proposed to affect host metabolism by influencing steroidogenesis and arachidonic acid metabolism pathways, which in turn regulate blood pressure through enhanced vascular function and decreased vascular remodeling. In summary, modulation of gut microbiota by SCFAs or a HF plays a protective role against PM2.5-induced hypertensive damages, suggesting a potential strategy to reduce environmental pollution-related cardiovascular risks through gut microbiota modulation.